The Influence of Financial Education and Lifestyle on Personal Financial Management Among Students - Sriyanti, S.; Asriany, A.; Ramadhan, Abid (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of financial education and lifestyle on personal financial management among university students. Unlike previous studies, this research focuses on students of the Sharia Economics Department at the State Islamic Institute of Palopo, Indonesia, examining both variables simultaneously to address inconsistencies in earlier findings. The study employs a quantitative approach, collecting data through the use of questionnaires. The results indicate that financial education has a positive and significant effect on personal financial management, where students with better financial knowledge tend to manage their finances more effectively. Additionally, a well-planned lifestyle also has a positive effect, with students who maintain one demonstrating better financial management. Regression analysis reveals that combining financial education with lifestyle significantly enhances personal financial management. These findings contribute new evidence to the literature by providing empirical results within the context of higher education in Sharia economics and offer practical recommendations for educational institutions to develop comprehensive financial literacy programs and encourage healthy lifestyle habits among students.